Упростить выражение 2cos 2 x-3sinX-3=0

0 голосов
183 просмотров

Упростить выражение
2cos 2 x-3sinX-3=0


Алгебра (17 баллов) | 183 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Формула:cos2x=1-2sin^2x\\2cos2x-3sinx-3=0 \to 4sin^2x+3sinx+1=0\\D=9-16=-7<0
Решений нет.
Но если косинус не с удвоенным углом, а имелось в виду квадрат косинуса, то решение такое:
cos^2x=1-sin^2x\\2cos^2x=2-2sin^2x\\2-2sin^2x-3sinx-3=0\\2sin^2x+3sinx+1=0\\D=9-8=1\\(sinx)_1=-1,x_1=-\pi +2\pi n,n\in Z\\(sinx)_2=-\frac{1}{2}, x_2=(-1)^k(-\frac{\pi}{6})+\pi k=(-1)^{k+1}\frac{\pi}{6}+\pi k, k\in Z

(835k баллов)